Economics, politics and ecology of biotechnology in Malaysian agriculture - Suntharalingam, Chubashini, author; Graff, Gregory, advisor; Byrne, Patrick, committee member; Thilmany, Dawn, committee member; Davies, Stephen, committee member (Colorado State University. Libraries, 2014)
Malaysia has been moving from an agricultural, resource extraction, and manufacturing based economy in the 1980s toward a service-oriented, post-industrial, knowledge-based economy, with greater emphasis on skilled human capital, technology, and intangibles. Assessing Malaysia's current economic and policy regimes are crucial to help chart the next course of actions for Malaysia to set its economic goals. The patent landscape analysis showed Malaysia's economy evolution over the past six decades. Primarily dependent on the chemicals and petroleum sector between 1953 and 1985, the economy, currently is dependent on two sectors, i.e., electronics, semiconductors and computing, and chemicals and petroleum. Generally, the commercial sector dominates the patenting activities in Malaysia, in the economy wide patenting arena and also in the agbiotech and agchemicals technologies. High patenting trends by foreign commercial entities is to avoid imitations to their inventions in the Malaysian market attributable to their high FDI investment and export share. Within the agricultural sector, patents in agbiotech are relatively low and overshadowed by patents in agchemicals. The higher number of agchemicals technologies patented in Malaysia is due to the long history of European MNCs in Malaysia. And, the low number of agbiotech patented in Malaysia, mainly by non-commercial entities is due to two reasons: (1) misalignment of policies promoting the use of modern biotechnology in the Malaysian agricultural sector, and (2) ecological risks of cultivating transgenic crops in Malaysia, a rich-biodiversity country. A political economy framework was utilized in understanding the misalignment of policies promoting the use of modern biotechnology and examining the influence of relevant stakeholder groups on the decision making process concerning regulations overseeing the cultivation of transgenic crops. Two Malaysian Giant conglomerates, Sime Darby Berhad and Felda Holdings Berhad, dominate world palm oil exports and local oil production, and inevitably, have a strong policy influence of the Malaysian agricultural sector. The world's two dominant agchemicals players, Bayer and BASF, also play a major role in the agricultural policy making process in Malaysia. Bayer is one of the leading players that dominate the agchemicals patents in Malaysia. BASF, meanwhile has formed a strategic alliance with the Malaysian Agricultural Research and Development Institute (MARDI) and developed a new herbicide resistant Clearfield rice variety to tackle weedy rice outbreak in Malaysia. These two special interest pressure groups, oil palm and agchemicals producers face large welfare impact if Malaysia adopts transgenic crops. With risk of losing their market shares in Malaysia and their relatively small number, these groups have been able to converge and exercise influence over the stalled commercialization process of transgenic crops. The other reason attributable to the low number of granted agbiotech patents in Malaysia pertains to ecological risk concerning deployment of transgenic organisms on Malaysia's rich biodiversity. Scientific assessments carried out on transgenic rice and papaya suggest that transgenic rice and papaya lines can potentially exert positive and/or negative ecological impacts, i.e., non-target organisms, transgene escape, heteroencapsidation, and RNA recombination. However, the studies reviewed in this dissertation call for long-term assessments to determine the longer term impact of transgenic rice and papaya on non-target organisms and transgene escape. In addition to this, majority of ecological studies carried out on non-target organisms have been limited to third trophic interaction. Considering the fact that Malaysia is a mega-diversity country, ecological studies concerning higher trophic level are required to assess the impact transgenic rice and papaya has on these populations and the food-web dynamics. Studies on heteroencapsidation and RNA recombination of papaya ringspot virus (PRSV) resistant transgenic papaya is also limited even though PRSV-resistant transgenic papaya has been in the market for over fifteen years. Ultimately, while transgenic rice and papaya do carry ecological risks, the decision to cultivate these crops lies on the benefits brought upon by these crops. World food supplies demand intensive crop production due to increased population growth, climate change, pest and disease challenges, political unrest, deterioration of soil quality, drought and flood. Ultimately, the benefits and challenges in cultivating transgenic crops need to be considered on a case-by-case basis. Cultivating transgenic crops has potential to decrease reliance on external inputs and reduce ecological risk. As such, until we can derive a balance between the two, we must strive to continue to improvise the transgenic technology to suit these two goals. For future research, it is recommended to determine the funding mechanisms of studies reviewed for the ecological assessments of transgenic rice and papaya in order to assess the objectivity of the study findings.
Keywords: transgenic rice; ecological risk; innovation; patent; political economy; transgenic papaya